Moisture Control Using A Low- Cost Experimental Approach For A Vertical Agricultural Indoor Module (Inflexion Point Magazine, 2024)
This paper describes an indoor vertical farming low-cost approach undertaken under experimental learning considerations. A structure measuring approximately one meter in height, 0.27 meters in width, and 0.38 meters in depth was constructed to examine the growth of arugula seeds. We equipped our vertical farming structure with emitters of artificial light in order to facilitate the photosynthesis of arugula plants that were planted in trays in a building without sufficient natural light. Further, soil moisture in the trays was monitored so that electromechanical water pumps were activated whenever a high level of soil dryness was detected. As a control unit, an ESP32 microcontroller was used. It was programmed to read sensors and to apply control signals as required. Additionally, ESP32 was configured to send data from sensors to an Internet of Things (IoT) web page, enabling us to monitor the system remotely. BIPES (Block-based Integrated Platform for Embedded Systems) is an intuitive programming tool that is available to the general  public through the internet, which was used for programming the ESP32. As a final aspect, researchers at the Universidad Distrital Francisco José de Caldas, the Corporación Universitaria Minuto de Dios, in Colombia, and the Universidade Federal of Sao Carlos, in Brazil, became interested in vertical farming as a topic to be involved in, leading to the development of a first approach which is presented in this paper.
Keywords: Indoor verfical farming; micropython; block based programming; ESP32; artificial light